Mobile Health Application Usage And Personnel Readiness For Hospital System Sustainability: Penggunaan Aplikasi Kesehatan Mobile Dan Kesiapan Personel Terhadap Keberlangsungan Sistem Rumah Sakit - Linda Wahyu Sekar Arum; Kosasih Kosasih; Ayu Laili Rahmiyati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Digital transformation drives hospitals to utilize modern technology for service efficiency and quality. Specific Background: Bintang Amin Hospital integrates digital health services like Mobile JKN with its internal hospital information framework. Knowledge Gap: The combined contributions of mobile application utilization and workforce preparedness to the long-term viability of hospital information systems require empirical evaluation. Aims: This study aimed to analyze the effects of Mobile JKN usage and human resource readiness on the sustainability of hospital management information systems at Bintang Amin Hospital, Bandar Lampung. Results: Using a quantitative descriptive-verificative approach with a sample of 78 medical and administrative personnel analyzed through multiple linear regression, findings showed that both mobile application usage and workforce readiness exerted positive and significant partial and simultaneous effects on system sustainability, with personnel readiness demonstrating a stronger regression coefficient of 0.942 compared to 0.501 for application usage. Novelty: This research integrates digital application metrics and workforce readiness into a unified empirical model to evaluate healthcare information management continuity. Implications: Hospitals must combine digital technology integration with continuous staff training and technical support to optimize sustainable digital health services. Highlights Workforce readiness demonstrates a stronger regression coefficient of 0.942 compared to 0.501 for mobile application usage regarding hospital system continuity. Multiple linear regression proves that application utilization and personnel preparedness simultaneously account for a 58.4% variance explanation of system sustainability. Empirical verification confirms that both digital tool adoption and staff competencies are vital for maintaining efficient electronic hospital administrative services. Keywords Mobile JKN; Human Resource Readiness; Hospital Information System; Digital Health; System Sustainability